2016
DOI: 10.1073/pnas.1525269113
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical reaction cycle transitions during anion channelrhodopsin gating

Abstract: A recently discovered family of natural anion channelrhodopsins (ACRs) have the highest conductance among channelrhodopsins and exhibit exclusive anion selectivity, which make them efficient inhibitory tools for optogenetics. We report analysis of flashinduced absorption changes in purified wild-type and mutant ACRs, and of photocurrents they generate in HEK293 cells. Contrary to cation channelrhodopsins (CCRs), the ion conducting state of ACRs develops in an L-like intermediate that precedes the deprotonation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
145
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(161 citation statements)
references
References 24 publications
16
145
0
Order By: Relevance
“…Previous studies have shown that the Glu68 → Gln substitution (E68Q) has significant effects on the channel gating mechanism 6 but only a weak effect on the visible absorption. 5,10 In agreement, at 80 K, UV–visible absorption of E68Q is very similar to that of WT (Figure S6A). However, the difference spectrum compared to that of WT (Figure 7 and Figure S6B) displays an increased negative intensity and a downshift in the wavelength of the major negative band (from 510 to 503 nm).…”
Section: Resultssupporting
confidence: 74%
See 4 more Smart Citations
“…Previous studies have shown that the Glu68 → Gln substitution (E68Q) has significant effects on the channel gating mechanism 6 but only a weak effect on the visible absorption. 5,10 In agreement, at 80 K, UV–visible absorption of E68Q is very similar to that of WT (Figure S6A). However, the difference spectrum compared to that of WT (Figure 7 and Figure S6B) displays an increased negative intensity and a downshift in the wavelength of the major negative band (from 510 to 503 nm).…”
Section: Resultssupporting
confidence: 74%
“…This result may indicate the K and L intermediates produced at 80 K exist in equilibrium, similar to the conclusion from room-temperature visible absorption measurements. 5 In addition, successive first-push decay difference spectra recorded at approximately 1 min intervals after the exciting light is turned off (Figure S3) reveal very little change compared to the initial “2–1” difference spectrum. This result eliminates the possibility that an L-like photoproduct corresponding to the 1545 cm −1 band is a transient species at 80 K that accumulates during illumination.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations